The Air Pollution Foundation and the Los Angeles Smog Problem - Neiburger, Morris (1955)
The paper was presented to the Los Angeles Chamber of Commerce's Research Committee.
Keywords: Hydrocarbons--Environmental aspects; Environmental sciences--Research; Motor vehicles--Pollution control devices; Los Angeles Chamber of Commerce; Air--Pollution